Recent Iranian Health System Reform: An Operational Perspective to Improve Health Services Quality - Mahdi Mahdavi; Mahboubeh Parsaeian; Ebrahim Jaafaripooyan; Shahram Ghaffari (Kerman University of Medical Sciences, 2018)
The operational management of healthcare services is expected to directly touch patient experiences. Iranian Ministry of Health and Medical Education (MoHME) for the first time, as such, has sought to improve the operational management of healthcare delivery within a reform agenda by setting benchmarks for 'number of visit per hour' and waiting time in outpatient clinics of about 700 affiliated hospitals. As a new initiative, it has faced with mixed reactions and various doubts have been cast on its successful implementation. This manuscript aims to shed some light on the operational challenges of the initiative and the requirements of its successful implementation.